Theorising and illustrating plural policing models in countering armed banditry as hybrid terrorism in northwest Nigeria - Oluwole Ojewale (Cogent Social Sciences)
Banditry constitutes about 40% of national insecurity in Nigeria. It is a composite crime manifesting in wanton killing, cattle rustling, kidnapping for ransom, levying of illegal tax on farming communities, sexual violence and trafficking of arms and drugs. Through qualitative and quantitative research methodology, this article attempts to theorise and illustrate policing models aimed at countering armed banditry in northwest Nigeria. Coordinates of attacks by bandits are georeferenced to show their spatial distribution and pattern. As Nigeria continues to experience the shocks of banditry, the national and subnational governments are providing counter measures to lessen the striking capability of the bandits through four distinct but complementary models of policing. The article offers direction on the policing imperatives for combatting armed banditry in Nigeria. It proposes a multilevel policing framework which encompasses the mainstream policing, hybrid policing and the joint task force models with the state police as the new layer on the existing security architecture. This is well suited to respond to the conceptual, practical and strategic dimensions of policing in Nigeria to combat armed banditry and other criminalities that envelop the country.